SPENDING AND SAVING PATTERNS OF TWO CONSUMER AGE GROUPS DURING ECONOMIC DOWNTURN AND RECOVERY OF 2009–2011 IN LITHUANIA - Pikturnienė, Indrė; Urbonavičius, Sigitas (Ekonomika, 2015)
Purpose. The purpose of the paper is to summarise and present differences in spending patterns between the two age groups (19–26 and 40–68) during the period of economic downturn and recovery. The method of longitudinal study allows finding how the expectations towards financial situation and spending behaviour change over three years (2009, 2010, 2011). This paper summarizes findings from the three years and expands the initial findings of the authors that have been published before (Urbonavičius, Pikturnienė, 2010).Methodology. The survey is based on a comparison of data from the three sets of respondents surveyed in spring of the 2009, 2010 and 2011, using the same questionnaire. Students, unaware of survey objectives, were asked to fill in questionnaires themselves and to distribute another part of the questionnaire to a member of their household, who is one generation elder (typically parents). In total, 455 households were interviewed, each producing two sets of answers to the survey questions.Results of the survey showed that younger respondents perceived the impact of the economic downturn in relation with expectations in a more casual way. They had higher expectations towards the income increase. Spending of both age groups, as well as their expectations towards prices were very similar throughout all the studied years. However, the older generation was more likely to save in order to survive, whereas the younger generation did not change its spending habits or decided to reduce spending for saving reasons.Practical implications. Since younger generation perceived the economic downturn situation more casually and reported a higher expected income, marketing strategies based on brand value, exclusivity, price premiums can be continued to target it even during the economic downturn. The older generation demonstrated a higher caution and frugality, as well as lower expectations towards income; therefore, value for price or lower price strategies could be more suitable for this age group.Value / originality. Longitudinal data on two age groups provide for a better understanding of the consumer behaviour during the economic downturn in general and in Lithuania in particular.
Keywords: economic downturn and recovery; consumer behaviour; consumer spending patterns; age groups